1986
DOI: 10.1002/pros.2990090405
|View full text |Cite
|
Sign up to set email alerts
|

The dihydrotestosterone (DHT) hypothesis of prostate cancer and its therapeutic implications

Abstract: Data are presented showing that human prostatic adenocarcinoma depends on dihydrotestosterone (DHT) and not testosterone (T) for growth. It follows that androgen ablative therapy should be directed toward elimination of DHT with retention of circulating T. This can be achieved by using a 5 alpha-reductase inhibitor such as 6-methyleneprogesterone (6-MP) (VII). Arguments are presented showing that 6-MP (VII) is expected 1) to function as a prophylactic agent against prostate cancer, 2) to represent an attractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

1988
1988
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 69 publications
0
26
0
2
Order By: Relevance
“…An¬ other androgen, namely mesterolone, is likewise unable to suppress gonadotropins (Petry et al estrogens (Wilson 1980(Wilson , 1987 and the lack of estradiol elevation under testosterone TTS may prevent prostatic growth. The role of testosterone and DHT in the origin of prostatic cancer remains controversial (Petrow 1986). The observation by Meikle & Stanish (1983) of low rather than high serum DHT levels in men at risk for prostatic carcinoma may even suggest a protective effect of DHT.…”
Section: Discussionmentioning
confidence: 99%
“…An¬ other androgen, namely mesterolone, is likewise unable to suppress gonadotropins (Petry et al estrogens (Wilson 1980(Wilson , 1987 and the lack of estradiol elevation under testosterone TTS may prevent prostatic growth. The role of testosterone and DHT in the origin of prostatic cancer remains controversial (Petrow 1986). The observation by Meikle & Stanish (1983) of low rather than high serum DHT levels in men at risk for prostatic carcinoma may even suggest a protective effect of DHT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, antiandrogens inhibit prostate growth in vitro (12) and in vivo (13). It is also known that, testosterone is irreversibly converted to dihydrotestosterone (DHT) within the prostate gland by the 5-␣a-reductase enzyme, and that DHT is the active androgen in the prostate (14). Human prostate growth is also regulated by growth factors such as epidermal growth factor (EGF), and it was recently shown that progression to prostate cancer is correlated with disruption of EGF signaling (15).…”
mentioning
confidence: 99%
“…Furthermore, it is postulated that testosterone that is converted peripherally to dihydrotestosterone (DHT) by 5-alpha reductase is responsible for this risk (Petrow, 1986) DHT has a role in the growth of prostatic tissue and therefore can infl uence lower urinary tract symptoms. Testosterone is aromatized to form estradiol (E2) in fatty tissue and leads to increased aromatase activity, resulting in increased levels of estradiol (Hudak et al, 2006).…”
Section: Discussionmentioning
confidence: 99%